Kedudukan Bank Perkreditan Rakyat Mengambil Alih Agunan Kredit Macet Melalui Lelang Atau Diluar Lelang - Siti Romlah; I Nyoman Putu Budiartha; I Made Aditya Mantara Putra (Jurnal Interpretasi Hukum, 2023)
Banks providing credit do not want non-performing loans, banks take preventive measures to prevent non-performing loans. Bank's efforts to settle non-performing loans by taking over the collateral for bad loans, either partially or wholly based on Article 12A paragraph (1) of the Banking Law. The purpose of the study was to determine the position of BPRs taking over bad credit collateral through auctions or outside auctions. The type of research is normative legal research with a statutory and conceptual approach. Legal materials consist of primary, secondary and tertiary legal materials, the collection of which is by literature study. Analysis with descriptive techniques, evaluation and argumentation. The results show that the position of BPR is not entitled to take over collateral either partially or completely through auction or outside the auction, the Banking Law only gives authority to Commercial Banks and legal consequences for BPRs that take over bad credit collateral through auction or outside the auction after the decision after the decision of the Constitutional Court no. 102/PUU-XVIII/2020 as referred to in Article 12 A paragraph 1 of the Banking Law which has been declared to have no binding legal force or is no longer valid, so that the authority of BPR is equal to that of Commercial Banks which can take over the collateral, either partially or completely, as collateral for bad loans. a form of equalization and legal protection for BPRs in carrying out banking activities